SNOWBALL THROWING MODEL FOR IMPROVING ISLAMIC RELIGIOUS EDUCATION LEARNING IN ELEMENTARY SCHOOLS - Suleman, Muh. Asharif; Idayanti, Zulfi; Hulkin, M.; Fadhil, Muhammad; Basri (STKIP Citra Bakti, 2024)
Increasing student participation in the learning process and improving their involvement in learning activities are important steps to make students more active and involved in the teaching and learning process. This study aims to increase student participation in Islamic Religious Education (PAI) learning in elementary schools using the snowball throwing model. The classroom action research (CAR) method used consisted of two cycles with two meetings each. The subjects of the study were 25 fifth grade students at Talaga Raya Elementary School. The researcher also acted as a teacher who implemented this learning model, with subject teachers as collaborators. Data were collected through observation of student learning activities. The results showed an increase in student participation from 69% in cycle I to 89% in cycle II. The snowball throwing model has proven effective in increasing student learning participation in PAI subjects.